Automatic Design of Robot Swarms: Achievements and Challenges - Francesca, Gianpiero; Birattari, Mauro (Frontiers in Robotics and AI, 2016)
Automatic design is a promising approach to the design of control software for robot swarms. In an automatic design method, the design problem is cast into an optimization problem and is addressed using an optimization algorithm. In this article, we review studies in which automatic design methods are successfully applied. In particular, we focus our attention on how automatic methods are empirically assessed. An apparent issue that emerges from our review is that a solid, well- established, and consistently applied empirical practice is still missing. For example, studies that propose new methods and ideas do not typically provide any comparison with existing ones. We maintain that the lack of a proper empirical practice hinders the progress of the domain. In this article, we pursue two goals: we highlight the notable achievements in the automatic design of control software for robot swarms and we discuss the challenges to be overcome to establish a proper empirical practice for the domain.